Consumer rights and legal guarantees in the European Union under Directive 1999/44/EC - Šaripo, Kristiāns (Riga Graduate School of Law, 2019)
In the modern world and united legislation across Europe consumer protection is becoming more influential and stronger. To everything positive there, of course, are drawbacks or so-called ‘’grey areas’’ which this research unveils. Because of certain principles set out by the European Union each country has the opportunity to create their own standards regarding guarantees and this research reveals to what extent consumer protection can go. To understand the reasoning for certain standards three countries are compared – Germany, Sweden, and the United Kingdom. With the use of different research methods and analysis answers to raised questions are found and concluded. Analyzing existing legislation, cases, comparing different countries and with help of economic analysis, it reveals what kind of problems are there regarding Directive 1999/44/EC and possible reasoning behind it. Also because of recent European Union problems with Brexit, it sets out valuable considerations and topic is connected with ongoing issues
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Consumer rights